COVID-19 Trials: Who Participates and Who Benefits?. Issue 4 (April 2022) - Narayanasamy, Shanti; Mourad, Ahmad; Turner, Nicholas A.; Le, Thuy; Rolfe, Robert J.; Okeke, Nwora Lance; O'Brien, Sean M.; Baker, Arthur W.; Wrenn, Rebekah; Rosa, Rossana; Rockhold, Frank W.; Naggie, Susanna; et al.
Abstract : The coronavirus disease 2019 (COVID-19) pandemic has had a disproportionate impact on older adults and racial and ethnic minority individuals in the United States. This article reviews a COVID-19 therapeutics trial conducted at the authors' institution to examine the low enrollment of groups particularly vulnerable to COVID-19. They reflect on the potential lack of impact that effective COVID-19 therapeutics may have on mortality if vulnerable groups are not enrolled in trials. Abstract: Objectives: The coronavirus disease 2019 (COVID-19) pandemic has disproportionately afflicted vulnerable populations. Older adults, particularly residents of nursing facilities, represent a small percentage of the population but account for 40% of mortality from COVID-19 in the United States. Racial and ethnic minority individuals, particularly Black, Hispanic, and Indigenous Americans have experienced higher rates of infection and death than the White population. Although there has been an unprecedented explosion of clinical trials to examine potential therapies, participation by members of these vulnerable communities is crucial to obtaining data generalizable to those communities. Methods: We undertook an open-label, factorial randomized clinical trial examining hydroxychloroquine and/or azithromycin for hospitalized patients. Results: Of 53 screened patients, 11 (21%) were enrolled. Ten percent (3/31) of Black patients were enrolled, 33% (7/21) of White patients, and 50% (6/12) of Hispanic patients. Forty-seven percent (25/53) of patients declined participation despite eligibility; 58%(18/31) of Black patients declined participation. Forty percent (21/53) of screened patients were from a nursing facility and 10% (2/21) were enrolled. Enrolled patients had fewer comorbidities than nonenrolled patients: median modified Charlson comorbidity score 2.0 (interquartile range 0–2.5), versus 4.0 (interquartile range 2–6) for nonenrolled patients ( P = 0.006). The limitations of the study were the low participation rate and the multiple treatment trials concurrently recruiting at our institution. Conclusions: The high rate of nonparticipation in our trial of nursing facility residents and Black people emphasizes the concern that clinical trials for therapeutics may not target key populations with high mortality rates.